2021
DOI: 10.3390/land10020116
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Perspective on Urban Sprawl: A Multidimensional Approach in Poland

Abstract: There are important relationships between the urban sprawl process and economic growth. They are usually expressed through spatial relations and changes taking place in the local, regional and national economy. The temporal and spatial dimension, including dispersed location, are the determinants of development and economic growth. Therefore, the urban sprawl phenomenon and the related location, hypothetically conditioning economic growth, should be subject to macroeconomic research. The article examines how u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…An important role in influencing the behaviour of space users is played by urban marketing, different information materials, promotions, location-based advertising, field meetings, social media campaigns etc. (Lityński and Hołuj 2018;2021). The effectiveness of soft impact instruments cannot always be predicted, so they are only used to support basic instruments.…”
Section: Externalities and Their Classification A Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…An important role in influencing the behaviour of space users is played by urban marketing, different information materials, promotions, location-based advertising, field meetings, social media campaigns etc. (Lityński and Hołuj 2018;2021). The effectiveness of soft impact instruments cannot always be predicted, so they are only used to support basic instruments.…”
Section: Externalities and Their Classification A Theoretical Backgroundmentioning
confidence: 99%
“…Reducing the occurrence of externalities in space involves an increased scope of market processes and a free transfer of the above-mentioned right. Therefore, Scitovsky's "interdependencies" should be defined more precisely based on a more detailed description of spatial management externalities [see: Hołuj, 2021]:…”
Section: Externalities and Their Classification A Theoretical Backgroundmentioning
confidence: 99%
“…In particular, using panel data from Chinese cities from 2014 to 2017, their analysis indicates that legal provisions can favor the increase in financial credit and foreign investment, in turn determining an increase in housing prices. Similarly, Lity ński and Hołuj [47] draw attention to the role of financial instruments, which can play a decisive role in stimulating the creation of compact spatial structures. In this group, attention should be paid to indirect instruments, such as tax exemptions or reliefs for new locations of compact housing.…”
Section: Exploring Practices From Europe and Beyond: A Roadmap For The Readermentioning
confidence: 99%
“…Moreover, with the increase of urban built-up areas in the urban sprawl process, numerous elements and resources are put into production activities, thereby reshaping and upgrading the economic bonus of the clustering effects in the urban sprawl context [4]. By contrast, other studies have concluded that urban sprawl harms local economic development [5,6]. High levels of urban sprawl are negatively associated with average labor productivity [7].…”
Section: Introductionmentioning
confidence: 99%